Microbioma de sedimentos de manguezais brasileiros e seu potencial biotecnológico - Bezerra, Walderly Melgaço (2015)
The assessment of microbial diversity associated to mangrove vegetation is the first step to better understand the plant-microorganism interactions in this ecosystem, as well as to reveal the biotechnological potential of this poorly explored microbiota. Therefore, this study aimed to investigate the microbial diversity of sediments associated to sediments of Rhizophora mangle rhizosphere by culture-independent methods and perform a data mining of biotechnological potential of microorganisms present in mangroves. Initially, bacterial 16S rRNA clone libraries of eight mangroves of Ceará’s state were constructed and sequenced by Sanger method. After the analysis, 663 sequences classified into 19 phyla of Bacteria were obtained. Acidobacteria, Bacteroidetes, Chloroflexi and Proteobacteria were detected in all of the eight mangroves. The current study also showed that the less anthropized mangrove (Timonha), used as a reference, presented the higher diversity of bacteria, whereas the most anthropized (Ceará) mangrove exhibited the lower richness, revealing the consequences of human impact on microbial diversity. Taking into account that the number of 16S rRNA clone libraries sequences obtained was not enough to cover the entire diversity of bacteria, we proceeded with more robust high-throughput sequencing in IlluminaTM MiSeq platform, including other mangroves from Northeast, North and South regions of Brazil. At least 3,717,347 sequences were obtained, distributed in 25,202 Operational Taxonomic Units (OTUs) at species level (> 97% similarity), covering 88% of the bacterial diversity (Good’s estimator). 71 phyla were detected, and among them, 14 were dominants, which means that they reached >1% of relative abundance. Proteobacteria was dominant with 63% relative abundance. Furthermore, this massive sequencing effort allowed the detection of a significant number of candidates and rare taxa, and most of them were first reported in mangroves. Prospection of biotechnological potential of amplicon libraries revealed mangroves habitats as a valuable source of bacterias recognized for producing enzymes, biosurfactants, antibiotics, antitumor substances etc. of biotechnological interest, such as those belonging to the phylum Actinobacteria